Investigación ambiental y conservación de la biodiversidad en zonas áridas y semiáridas del sur de la provincia de El Oro - Feijoo Yaguana, Karla Elizabeth; León Cueva, Carla Estefanía (Machala: Universidad Técnica de Machala, 2021)
The southern part of Ecuador has a great diversity of ecosystems which are understood as the variety of communities of organisms that occur in certain areas, including the different species that compose them and the ecological processes that they perform Aguirre Mendoza, Aguirre Mendoza, & Muñoz Ch., 2017. These ecosystems include the arid and semi-arid zones in the province of El Oro, specifically in the cantons of Arenillas and Huaquillas, which are areas that possess unique characteristics for the development of floristic and faunistic species of these areas. It is important to mention that this work was carried out with three structural components. Chapter 1, refers to the conceptions, applicable legal regulations and diagnostic approach, which was based on a qualitative-quantitative approach as a process to be carried out for the collection, analysis and linking of data and therefore, different types of research were applied such as: exploratory research, descriptive research and explanatory research. In addition, primary and secondary information was collected. For primary information, the interview was the technique used, which was done to different actors with knowledge in the environmental and territorial area, and as secondary information, a baseline was executed considering the main physical factors, social, economic, cultural and environmental aspects of the study area, that is, the cantons of Arenillas and Huaquillas. For the analysis of the context of the study area, the SWOT matrix was applied as a methodology, which allows us to identify the strengths, opportunities, weaknesses and threats of the study area, in addition to describing each of these characteristics, in order to better approach the proposal for this integrating project. The realization of this matrix also helped to synthesize in a better way a matrix of requirements, where the main problems raised were: The lack of scientific research in the socioeconomic and environmental area of the study area, loss of natural and endemic species in the area and growth of anthropic activities within the study area. In chapter 2, the integrative proposal was made that consists in the design of an environmental interpretation center in the arid and semi-arid zones of the southern region of Ecuador, located in the parish of Chacras, canton Arenillas, province of El Oro, The Commission has also proposed three specific objectives based on the development of a baseline for the area of study, the description of the structural components and, finally, a structural plan for the interpretative centre. In chapter 3, the feasibility analyses of the technical, economic, social and environmental factors were carried out. Once the evaluation tools have been applied according to each factor analysed, it has been concluded that the proposal is viable for each of them. Finally, it is important to know that the proposal has been proposed with the aim of developing scientific projects, generating plans for the restoration and conservation of the floristic and faunistic species of these areas and increasing environmental education.
Capítulo 1, se hace referencia a las concepciones, normativa legal aplicable y enfoque diagnóstico, el cual se basó en un enfoque cuali-cuantitativo como un proceso a llevar a cabo para la recolección de datos, el análisis y la vinculación de los mismos y por ello, se aplicaron diferentes tipos de investigación tales como: investigación exploratoria, investigación descriptiva y la investigación explicativa. Además, se realizó la recolección de información primaria y secundaria. Para la información primaria, la entrevista fue la técnica utilizada, misma que se realizó a diferentes actores con conocimiento en el área ambiental y territorial, y como información secundaria, se ejecutó una línea base considerando los principales factores físicos, sociales, económicos, culturales y ambientales de la zona de estudio, es decir, de los cantones de Arenillas y Huaquillas. Para el análisis del contexto de la zona de estudio, se aplicó como metodología la matriz FODA, las cual nos permite identificar las fortalezas, oportunidades, debilidades y amenazas de manera general del área de estudio, además de ir describiendo cada una de estas características, con la finalidad de enfocar de mejor la manera la propuesta para el presente proyecto integrador. La realización de esta matriz también ayudó a sintetizar de una mejor manera una matriz de requerimientos, en donde los principales problemas planteados fueron: La falta de investigación científica en el ámbito socioeconómico y ambiental de la zona de estudio, pérdida de especies naturales y endémicas de la zona y el crecimiento de las actividades antrópicas dentro del área de estudio. En el capítulo 2, se realizó la propuesta integradora que consta en el diseño de un centro de interpretación ambiental en las zonas áridas y semiáridas de la región sur del Ecuador, ubicado en la parroquia Chacras, cantón Arenillas, provincia de El Oro, mismo que se ha planteado con la ayuda de tres objetivos específicos que se basan en la elaboración de una línea base del área de estudio, la descripción de los componentes estructurales y por último, un plan estructural del centro interpretativo. En el capítulo 3 se procedió a realizar los análisis de factibilidad del factor técnico, económico, social y ambiental. Una vez aplicadas las herramientas de evaluación acorde a cada factor analizado, se ha concluido que la propuesta es viable con respecto a cada uno de ellos. Y, por último, es importante conocer que la propuesta ha sido planteada con el objetivo de desarrollar proyectos científicos, generar planes para la restauración y conservación de las especies florísticas y faunísticas propias de estas zonas e incrementar la educación ambiental.
Keywords: ZONA ARIDA; DISEÑO; SEMIARIDA; NTERPRETACION AMBIENTAL